Identification of Whirly transcription factors in Triticeae species and functional analysis of TaWHY1-7D in response to osmotic stress - Liu, Hao; Wang, Xiaoyu; Yang, Wenbo; Liu, Wenyan; Wang, Yanfang; Wang, Qin; Zhao, Yanhong (Frontiers in Plant Science, 2023)
Osmotic stress poses a threat to the production and quality of crop. Whirly transcription factors have been investigated to enhance stress tolerance. In this study, a total of 18 Whirly genes were identified from six Triticeae species, which were classified into Whirly1 and Whirly2. The exon-intron structure, conserved motif, chromosomal location, collinearity, regulatory network of Whirly genes were also analyzed. Real-time PCR results indicated that TaWHY1 genes exhibited higher expression levels in leaf sheaths and leaves during seedling stage, while TaWHY2 genes were predominantly expressed in roots. Under PEG stress, the expression levels of TaWHY1-7A, TaWHY2-6A, TaWHY2-6B and TaWHY2-6D were increased,